Formulating Business Development Strategies for Medium Enterprises: A Case Study of CV Aneka Sumber Rezeki - Firdaus, Reza; Triyono, Sunu Puguh Haru (eProceedings of Management, 2025)
CV. Aneka Sumber Rezeki is a company engaged in the snack food industry and faces challenges in increasing competitiveness in an increasingly competitive market. The emergence of new competitors has resulted in a drastic decline in the company's turnover.This study aims to identify internal and external factors, formulate and determine strategies as appropriate development strategies.The research method used is a qualitative approach through interviews, observations, and questionnaires involving internal and external parties of the company to gain an in-depth understanding of business conditions.The analysis was carried out using IFE and EFE matrices to assess internal and external factors, IE Matrix to determine the company's strategic position aimed at knowing alternative strategies, and QSPM to choose the right strategy to respond to company needs.Based on the results of the analysis, CV Aneka Sumber Rezeki is in the Growth and Build category, which indicates the need for a market development strategy as a top priority. This strategy focuses on entering new markets beyond their current distribution areas through comprehensive market analysis and utilization of e-commerce platforms. The implementation of this strategy is expected to increase the company's competitiveness by expanding the customer base, strengthening brand image, and increasing operational efficiency by digital technology. With proper implementation, CV Aneka Sumber Rezeki can take advantage of existing opportunities and face the challenges of a more adaptive and sustainable industry. Keywords – IFE Matrix, EFE Matrix, Development Strategy, IE Matrix, QSPM